Desing and implementation of a SCADA software to the cema temperature module - Chung Pinzás, Alfonso (2011)
The article shows the results of the research project that had like main objective design and implements a SCADA software in the CEMA temperature module; at the end of the project we develop own technology that finished in a SCADA software will be used in the course Units Operations, as well as a laboratory guide to can help to the students to make their own software.